The Ethnographic State : France and the Invention of Moroccan Islam - Burke, Edmund, III, 1940- (Book collections on Project MUSE., 2014)
Alone among Muslim countries, Morocco is known for its own national form of Islam, ""Moroccan Islam."" However, this pathbreaking study reveals that Moroccan Islam was actually invented in the early twentieth century by French ethnographers and colonial officers who were influenced by British colonial practices in India. Between 1900 and 1920, these researchers compiled a social inventory of Morocco that in turn led to the emergence of a new object of study, Moroccan Islam, and a new field, Moroccan studies. In the process, they resurrected the monarchy and reinvented Morocco as a modern polit.